Is the Rural-Access-Index (RAI) a Reflection of Rural and Urban Poverty? A Data Analysis - Alba, Charles (International Journal of Social Science and Business, 2020)
While there are plenty of studies to support that infrastructural developments aimed at enhancing accessibility do reduce both rural and urban poverty, it is not tied to any global indicator. This is concerning for planners and policy analysts, especially those in developing nations, for they do not have a reflective indicator to rely on when attempting to optimize resource allocation towards accessible infrastructure development. Hence, in this paper, we aim to assess if the Rural Access Index (RAI) accurately reflects a nation's rural and urban poverty levels. This is based on the concept that accessibility is key to eradicating poverty. We do so by performing a regression analysis on the RAI against Rural and Urban Poverty. Our analysis determines that the RAI does indeed reflect Rural and (the square-root of) Urban poverty in relation to infrastructural development. Thus, the RAI could aid national planners and authorities in roadway infrastructural planning. It could thus be used as a specialized indicator towards the optimal allocation of resources for infrastructural developmental purposes aimed at eradicating rural and urban poverty through rural accessibility.